Magnus Stevns: Fra Grundtvigs salmeværksted - Møller, Niels (Grundtvig-studier, 1951)
Magnus Stevns: Fra Grundtv igs Salmeværksted (From the hymnstudio of Grundtv ig) . Udgiv e t af H enning Høirup og Steen Johansen. København 1950. Re v iewed b y Nie l s Møller. This collection of essays on Grundtvig’s hymns by Magnus Stevns, whose work as an editor of the hymns was cut short by his untimely death, is to be regarded as a monument in honour both of Grundtvig and of Stevns himself, who was richly endowed with the qualities required in the ideal interpreter of Grundtvig, especially a strong spiritual affinity with him. Stevns begins as an essentially aesthetic critic, but ends as a convinced preacher of the peculiar Grundtvigian views and principles of Christianity and humanity. Two special theses seem characteristic of Stevn’s investigations: 1) that Gr. belongs to the type of poets who tend to react against their predecessors and models rather than to imitate them; 2) that Gr. in his hymns fixes his eye on the path of victory beyond the Cross towards the glory of Heaven, while his predecessors in Danish hymnody look mostly at the path of obedience and self-sacrifice leading towards the Cross. Lastly, some minor mistakes in the essays are demonstrated. But even where such errors occur, the main drift of the several essays and the many valuable observations which they contain will make the studying of them really worth while.